Návrh optimální konkurenční strategie pro tržní segment dveřní kování - Nytrová, Jana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Diplomová práce popisuje současnou situaci podniku na trhu a jeho konkurence. Obsahuje návrh optimální konkurenční strategie pro tržní segment dveřní kování pro ČR, který by vedl k udržení či posílení pozice na trhu.

The master’s thesis describes current situation on the market and its competition. It contains the proposal of an optimal competitive strategy for market segment „door fittings“ for the Czech Republic which should lead to maintenance of the position of the company or to reinforce its position on the market.
Proposal of the Optimal Competitive Strategy for „Door Fittings“ Market Segment
Keywords: SLEPT analýza; SWOT analýza; konkurenční strategie; konkurenční výhoda; SLEPT analysis; SWOT analysis; competitive strategy; competitive advantage